β-Neoendorphin Enhances Wound Healing by Promoting Cell Migration in Keratinocyte - Dong Joo Yang; Sang Hyun Moh; Yun-Hee Choi; Ki Woo Kim (Molecules, 2020)
The skin is the largest and a remarkably plastic organ that serves as a protective barrier against environmental stimuli and injuries throughout life. Skin injuries are serious health problems, and wound healing is a critical process to replace devitalized cellular and tissue structures. Although some endogenous opioids are known to be involved in the modulation of wound healing, it remains to be determined whether the β-neoendorphin (β-NEP), an endogenous opioid, has beneficial effects on wound repair in human keratinocyte. In this study, we found that β-NEP accelerated wound repair through activation of mitogen-activated protein kinase (MAPK)/Erk1/2 signaling pathways in human keratinocytes. Moreover, the wound healing effect of β-NEP is mainly through the acceleration of keratinocyte migration without affecting cell proliferation. Therefore, our studies reveal that β-NEP plays an important role in the regulation of wound repair and suggest a therapeutic strategy to promote wound healing using β-NEP.